Poetry as a means of social criticism and medium for learning literature in high school - Diplan, Diplan (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
The message of criticism can be conveyed in various ways, one of which is through the medium of poetry. As a literary work, poetry conveys a message in a series of beautiful languages, short but full of meaning, and able to touch the feelings of its readers. This research examines a poem entitled Selfish by Misnawati. In this poem, there is a social critique of the phenomenon of selfishness that occurs in modern society without leaving aesthetic value with the use of metaphors that can touch the reader's feelings. This study aims to explore the use of metaphors in poetry that convey social criticism and its implications for learning literary works. The method used in this study is a literature study with a semiotic design to identify the metaphorical meaning contained in the poem. Analysis data is in the form of words, phrases, or expressions that contain metaphors. The results of this study show that the use of metaphors in this poem was created to strengthen the message or meaning of social criticism so that it can foster social awareness, feelings of empathy, critical thinking, develop creativity, and foster the reader's sense of aesthetics. The implications of these findings can be used in literary learning in the framework of (1) fostering students' social awareness, (2) improving students' literary ability, (3) arousing student empathy, (4) developing student creativity, and (5) fostering students' critical awareness.